Exposure to anti-seizure medication during pregnancy and the risk of autism and ADHD in offspring: a systematic review and meta-analysis - Xu, Shan-Chun; Zhong, Ying; Jiang, Hai-Yin; Tang, Jun (Frontiers in Neurology, 2024)
Background Evidence of an association between maternal use of anti-seizure medication (ASM) during pregnancy and the risk of autism spectrum disorder (ASD) or attention-deficit/hyperactivity disorder (ADHD) in children is conflicting. This systematic review and meta-analysis aimed to summarize the relationship between fetal exposure to ASM and the development of ASD or ADHD in offspring. Methods A comprehensive literature search was conducted in PubMed and other databases to identify relevant epidemiological studies published from inception until 1 March 2024. Results Seven cohort studies were included in the meta-analysis. The results showed that maternal exposure to ASMs during pregnancy was associated with an increased risk of ASD [odds ratio (OR): 2.1, 95% confidence interval (CI): 1.63–2.71; p < 0.001] in the general population. This association became weaker (ASD: OR: 1.38, 95% CI: 1.11–1.73; p = 0.004) when the reference group was mothers with a psychiatric disorder or epilepsy not treated during pregnancy. Furthermore, an increased risk of ADHD was observed when the study data adjusted for drug indications were pooled (OR: 1.43, 95% CI: 1.07–1.92; p = 0.015). In subgroup analyses based on individual ASM use, only exposure to valproate preconception was significantly associated with an increased risk of ASD or ADHD. Conclusion The significant association between maternal ASM use during pregnancy and ASD or ADHD in offspring may be partially explained by the drug indication or driven by valproate.